Pemanfaatan Looker Studio untuk Visualisasi Kinerja Program Studi D4 Teknik Multimedia dan Jaringan - Ainun Jariyah; Irmawati Irmawati; Tantri Indrabulan; Muhammad Ilyas Syarif; Riesa Krisna Astuti Sakir (Universitas Pahlawan Tuanku Tambusai, 2022)
The Internal Quality Audit (IQA) process provides information related to performance of Study Program, this performance is represented by twelve criteria based on IQA instrument. The problem is Study Program team describes every condition of the twelve performance achievements in narrative and graphical form using Microsoft Excel and presented to audit team, this’s less effective because Study Program team's explanation cannot be accessed either online or in real time. Alternative solution is the creation of dashboard become right solution to visualize data related to Study Program performance by online so that it is easily accessible to interested parties. The method used is identifying dashboard needs, starting making and presenting dashboard, as well as testing and evaluating. The result is dashboard using Looker Studio which is presented in web view using Google Site to visualize Study Program performance which is illustrated through four criteria, namely lecturers, students, research, and community service whose function is to answer several IQA question instruments related to these criteria. The conclusion is the dashboard successfully answers IQA questions regarding parameters of Study Program performance for 4 criteria, and also presentation of the dashboard on Google Site makes monitoring performance data for each criterion easier to analyze. Keywords: dashboard, google site, looker studio, online, visualization